Malignant skin melanoma in Croatia - Materljan, Eris; Zamolo, Gordana; Petković, Marija; Ivošević, Dejan; Popović, Branislava, liječnica; Materljan, Mauro; Katunarić, Miljenko; Jurišić, Davor, liječnik (2009)
Abstract: Global heating and increased solar ultraviolet irradiance have caused an increase in number of many diseases, particularly skin malignant diseases. Aim of this study was to investigate the influence of climate changes on the health of the population of the Primorsko-goranska and Istria Counties. We gathered and analyzed data about the frequency of skin malignant melanoma in the period of eight years (1998–2005). The data were collected from the Croatian cancer registry. The incidence of malignant skin cancer was estimated overall, by age group and gender. We found that the incidence of the skin melanoma was approximately the same in both counties during the period 1998–2005. However, significant increase has been noted when compared to the situation in the period 1977–1996 (p=4.95 E–13) The incidence of malignant skin melanoma has risen during the last ten years. It is differently distributed between gender and age groups in Primorsko-goranska and Istria County. It can be related to climate changes, but also to different ways way of life between these two counties
Bibliografija
Sažetak
Keywords: Maligni melanom kože -- Klimatske promjene; Hrvatska